2010
DOI: 10.1128/iai.00600-10
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Immune Tolerance toPorphyromonas gingivalisLipopolysaccharide Promotes Neutrophil Migration and Decreased Apoptosis

Abstract: Periodontitis, a chronic inflammatory disease of the tissues supporting the teeth, is characterized by an exaggerated host immune and inflammatory response to periopathogenic bacteria. Toll-like receptor activation, cytokine network induction, and accumulation of neutrophils at the site of inflammation are important in the host defense against infection. At the same time, induction of immune tolerance and the clearance of neutrophils from the site of infection are essential in the control of the immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 37 publications
3
38
0
Order By: Relevance
“…Interestingly, the proinflammatory cytokine IL-8 was present at similar levels for all three HK bacterial stimulations and remained at higher levels for several hours. The potency of all three HK bacterial species alone or in combination with respect to cytokine excretion is consistent with data from previously reported studies (4, 40, (52). In their study, Escherichia coli LPS-tolerized THP-1 monocytes had reduced levels of IL-8 excretion with repeated LPS challenges, whereas P. gingivalis-tolerized monocytes did not.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, the proinflammatory cytokine IL-8 was present at similar levels for all three HK bacterial stimulations and remained at higher levels for several hours. The potency of all three HK bacterial species alone or in combination with respect to cytokine excretion is consistent with data from previously reported studies (4, 40, (52). In their study, Escherichia coli LPS-tolerized THP-1 monocytes had reduced levels of IL-8 excretion with repeated LPS challenges, whereas P. gingivalis-tolerized monocytes did not.…”
Section: Discussionsupporting
confidence: 81%
“…Markedly, the stimulation of IL-1␤ secretion by P. gingivalis, T. denticola, and T. forsythia may be an important mechanism that amplifies the inflammatory response, the induction of connective tissue-degrading enzymes, and osteoclastic alveolar bone resorption (26). Furthermore, IL-8 as well as RANTES aid neutrophil, monocyte, and TH 1 cell recruitment to the site of infection (35,52). Previously, cytokine expression was observed for infection with HK P. gingivalis, T. denticola, and T. forsythia, but there has been no report on the effect of live bacterial infection on undifferentiated THP-1 monocytes (4,40).…”
Section: Discussionmentioning
confidence: 99%
“…We have already reported that impaired immune tolerance to P. gingivalis LPS is responsible for neutrophil-dominated chronic inflammation seen in periodontitis (25). In the current study we show that in contrast to E. coli LPS-induced tolerance, which is characterized by the down-regulation of human IL-8 and TNF-␣ and mouse KC, MIP-2, and TNF-␣ production, P. gingivalis LPS-pretreated human monocytes and mouse bone marrow-derived macrophages remained able to secret IL-8 and KC and MIP-2, respectively, but production of TNF-␣ was significantly decreased.…”
mentioning
confidence: 99%
“…Although macrophages have been shown to release higher amounts of catecholamines, infiltrating neutrophils are in a higher abundance during periodontitis [95,96] and are more likely to have an effect on periodontal microbes like A. actinomycetemcomitans due to their release of catecholamines. Therefore, a better understanding of how oral bacteria, specifically A.…”
Section: Microbial Endocrinologymentioning
confidence: 99%